GENDER CHARACTERISTICS OF THE PRESENTATION OF PROFESSIONAL DEFORMATION IN PRIMARY TEACHERS (Universal International Scientific Journal, 2026)
This article analyzes the factors of professional deformation in primary school teachers and their gender characteristics. Psychological changes, professional fatigue and stereotypes that occur in male and female teachers during their pedagogical activity are scientifically covered. The impact of professional deformation on the educational process and psychological and pedagogical methods of preventing it are also considered.
Keywords: professional deformation; pedagogical activity; gender characteristics,